2009
DOI: 10.1007/s12552-009-9019-x
|View full text |Cite
|
Sign up to set email alerts
|

Are Blacks and Hispanics Disproportionately Incarcerated Relative to Their Arrests? Racial and Ethnic Disproportionality Between Arrest and Incarceration

Abstract: Do large racial and ethnic disparities in prison populations reflect systematic racial and policy discrimination in the criminal justice system, or do they reflect disproportionate involvement of blacks and Hispanics in “serious” or street crime? Our investigation of this question keys off the approach initiated by Alfred Blumstein is his pioneering studies on the topic. While yielding important findings, there are, however, substantial gaps in the empirical literature on the racial disproportionality issue. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 19 publications
(51 reference statements)
0
26
1
Order By: Relevance
“…There is evidence that Black-White disparities in state and federal court dispositions to prison in the 1980s and 1990s are substantially reduced after one takes into account criminal history and the seriousness of arrest charges (Langan 1985; 2001; Klein, Petersilia, and Turner 1990). More recent studies using Pennsylvania (Harris, Steffensmeier, Ulmer, and David 2009) and federal sentencing data (see Sorensen, Sarnikar, and Oaxaca 2012; Starr and Rehavi 2012) from the 2000s reaffirm earlier work and suggests that differences in offense severity and criminal history continue to explain a substantial share of Black-White disparities in prison rates. A meta-analysis of research on racial disparities in criminal court dispositions finds that studies that controlled for offense severity or criminal history estimated lower racial disparities (Mitchell 2005).…”
Section: Prior Literaturementioning
confidence: 75%
See 1 more Smart Citation
“…There is evidence that Black-White disparities in state and federal court dispositions to prison in the 1980s and 1990s are substantially reduced after one takes into account criminal history and the seriousness of arrest charges (Langan 1985; 2001; Klein, Petersilia, and Turner 1990). More recent studies using Pennsylvania (Harris, Steffensmeier, Ulmer, and David 2009) and federal sentencing data (see Sorensen, Sarnikar, and Oaxaca 2012; Starr and Rehavi 2012) from the 2000s reaffirm earlier work and suggests that differences in offense severity and criminal history continue to explain a substantial share of Black-White disparities in prison rates. A meta-analysis of research on racial disparities in criminal court dispositions finds that studies that controlled for offense severity or criminal history estimated lower racial disparities (Mitchell 2005).…”
Section: Prior Literaturementioning
confidence: 75%
“…Research consistently finds that the size of the racial disparities in prison commitments is sensitive to the inclusion of characteristics such as current offense type and prior criminal history (Klein et al 1990; Kramer and Steffensmeier 1993; Steffensmeier and Demuth 2000; Langan 2001; Harris, Steffensmeier, Ulmer and Davis 2009; Starr and Rehavi 2012). To properly identify Black-White disparities in prison commitments, one needs to appropriately account for the confounding effect that current case characteristics and criminal histories may have in determining prison dispositions.…”
Section: Prior Literaturementioning
confidence: 99%
“…In this latter scenario, bias can come in many forms and can be exercised by many different actors (see also Frase, 2009). While there are significant data limitations that impede our ability to fully decompose aggregate racial disparities in incarceration rates (Frase, 2010), the available data indicated that during the 1970s and 1980s little of this disparity was due to sentencing differentials and a large majority--75-80%--was due to differential selection into the criminal justice system, namely racial disparities in rates of offending and arrest (Blumstein, 1982(Blumstein, , 1993Harris, Steffensmeier, Ulmer, & Painter-Davis, 2009;Langan, 1985). Times have changed, however.…”
Section: Understanding Racial Inequality In Incarceration Ratesmentioning
confidence: 99%
“…The chances of ever being incarcerated for Black men in the USA are nearly 29 %, compared to less than 5 % for White men [59]. Likewise, transgender people irrespective of race are overrepresented in American state prisons [60].…”
Section: Discussionmentioning
confidence: 99%